Efficacy of Higher Cutting Rates during Microincision Vitrectomy for Proliferative Diabetic Retinopathy. Issue 4 (July 2016) - Sano, Masahiko; Inoue, Makoto; Itoh, Yuji; Hirota, Kazunari; Koto, Takashi; Hirakata, Akito
Purpose: To compare the outcomes of 25-G vitrectomy using a vitreous cutter with a higher cutting rate to that of conventional 25-G vitrectomy with a lower cutting rate on eyes with severe proliferative diabetic retinopathy (PDR). Methods: The medical records of 393 eyes of 326 patients with severe PDR were reviewed. A higher cutting rate dual-pneumatic 25-G vitrectomy probe (5, 000 cuts/min, Constellation) was used on 219 eyes (group C) and a conventional 25-G pneumatic vitrectomy probe with lower cutting rate was used on 174 eyes (2, 500 or 1, 500 cuts/min, Acurrus) (group A). The visual and anatomical outcomes and the incidences of intraoperative and postoperative complications were compared. Results: The incidence of combined cataract surgery was significantly higher in group C (p<0.001). The number of eyes in which scissors were used was significantly lower in group C (p<0.001), and the use of perfluorocarbon liquid was higher in group C (p = 0.015). The incidence of intraoperative iatrogenic tears, postoperative retinal detachments, and neovascular glaucoma was not significantly different between the 2 groups, but the incidence of postoperative vitreous hemorrhage was significantly lower in group C eyes (p<0.001). Preoperative and postoperative vision were not significantly different between the 2 groups. Conclusions: The higher vitreous cutting rates during 25-G vitrectomy make it easier to dissect fibrovascular membranes with only the vitreous cutter, and achieved equivalent anatomical and visual outcomes after 25-G vitrectomy for PDR.